The harmony search optimisation method as applied to high dose rate brachytherapy - Mason, Lara (My University, 2019)
This research report presents an investigation into the dose calculation used for planning of high dose rate brachytherapy treatment for cervical cancer using Monte Carlo methods, including the implementation of a novel optimisation algorithm, the Harmony Search method. The optimisation is implemented using the Geant4 Monte Carlo simulation toolkit. Monte Carlo methods are also applied to the investigation of the AAPM TG-43 parameters, which deﬁne the dose calculation formalism used in high dose rate brachytherapy treatment planning. The parameters of the AAPM TG-43 protocol are calculated and compared to data. The Harmony Search algorithm is successfully implemented in optimising a brachytherapy treatment plan, and produces an optimal solution which ﬁts the constraints imposed on it. The algorithm shows promise in future application to brachytherapy for cervical cancer treatment planning.
Aresearch reportsubmitted totheFaculty ofScience, Universityof theWitwatersrand,Johannesburg, in partial fulﬁlment of the requirements for the degree of Master of Science in the Department of Physics, January 2019